Languages We Live By : Exploring Sociolinguistic Trajectories - Katrin Ahlgren; Clara Molina (Multilingual Matters, 2026)
This book invites readers to reflect on the impact of languages and create workshops to develop inclusive and responsible societies. Language plays a crucial role in the creation and reproduction of social inequalities, but it can also be a key factor in their deconstruction and in the creation of a more multilingual and inclusive world. This book guides the reader through an exploration of creative and effective tools for examining the role that languages play in the life trajectories of speakers and how they can shape personal identities and promote social justice. The authors demonstrate the use of personal language family trees, language self-portraits and autobiographical narratives as means to explore sociolinguistic repertoires and language use in various contexts. Written in an accessible, jargon-free way, with real-life examples from speakers of diverse geographical backgrounds, the book will be of interest both to scholars and students embarking on a study of the intersections between language and social justice, and to language teachers and learners who wish to explore the role that languages play in their lives. This book is open access under a CC BY NC ND licence.